Accurate voltage measurement by the quadrature method. - Chavez, P.P (IEEE Transactions on power delivery)
This paper introduces the quadrature method for measuring voltage using one or more electric field sensors. To date, all high-voltage sensors, from conventional inductive transformers to modern optical voltage transducers, have one or more of the following traits in common: large size and weight, high-voltage electrodes in close proximity, expensive and potentially hazardous insulation, and capacitive voltage division. Combined with the use of small electro-optic field sensors, the quadrature method enables voltage sensor designs that are free of these traits and that are, therefore, particularly ideal for high-voltage applications. It also allows for a trade-off between the accuracy of the voltage measurement and the number of required electric field sensors. Numerical simulations demonstrate the effectiveness of this technique.